Interleukin 12 induces the differentiation of major histocompatibility complex class I-primed cytotoxic T-lymphocyte precursors into allospecific cytotoxic effectors. - Chouaib, S (1994)
The production of interleukin 12 (IL-12) following allogeneic stimulation and its involvement in the differentiation of allospecific cytotoxic T lymphocytes (CTLs) have been investigated. Supernatants of mixed lymphocyte cultures had detectable levels of IL-12 p40 which were completely abrogated after depletion of responder cells from monocytes. While addition to the culture of anti-IL-12 neutralizing antibodies partially inhibited the allogeneic proliferative response and the subsequent CTL activity, addition of IL-12 stimulated both responses, suggesting that endogenously produced IL-12 plays a role in the development of alloreactivity. Furthermore, using primary mixed cultures of lymphocytes from major histocompatibility complex-recombinant siblings identical for class II antigens and displaying class I disparity, we demonstrated that addition of recombinant IL-12 at the sensitizing phase of the primary mixed lymphocyte culture induced CTL activity. Under these stimulation conditions, addition of recombinant IL-12 also triggered cell proliferation, indicating that IL-12 provides both growth and differentiation signals. The mechanism underlying this process does not appear to require IL-2, since IL-12-mediated CTL generation was not abrogated by anti-IL-2 alpha-chain antibodies. IL-12 increased granzyme B and perforin mRNA accumulation in major histocompatibility complex class I-primed lymphocytes, suggesting that this cytokine activates these two genes in CTL precursors. We conclude that IL-12 can stimulate the generation of alloreactive CTLs. We suggest that IL-12 may play a role in helper cell-independent CTL generation.